Shoot level fall current annual growth on experimental plots in Yellowstone's Northern Range, 2002-2015 - Hobbs, Tom; Kotter, Dan (Colorado State University. Libraries, 2016)
Data file and metadata sheet for column fields.
Zip file includes: data; metadata files with metadata for column fields.
Natural Resource Ecology Laboratory (NREL)
Keywords: willow; biomass; production; browse intensity